Crop residue trade-offs project: Tools lessons and gaps - International Livestock Research Institute (International Livestock Research Institute, 2010)
From 9-10 December 2010, Researchers in a project carrying out four regional cases studies of 'crop residue trade-offs in crop–livestock systems' met in Addis Ababa to review progress and plans. We recorded the reporting back sessions that discussed lessons and gaps related to the content focus of the project, the process followed so far, and the tools used. Here, Nils Teufel reports on the tools and technical software used in the project, including SPSS, CSPRO, Google Earth. A big issue across the tools was training and we need to, for instance, draw on people with specialist knowledge across the project. Data management and archiving was discussed and some lessons from the questionnaires and survey tools were derived. The meeting was organized by the CGIAR Systemwide Livestock Programme (SLP).